Adolescents’ right to sexual and reproductive health components (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Adolescents’ right to sexual and reproductive health contains a set of entit-lements that include the provision of appropriate and specific services to address ef-fectively their sexual and reproductive health needs and the right to respect for their autonomy (access to information and confidential counseling, responsible choices) in accordance with their evolving capacities, in the context of the tripartite adolescent – healthcare staff – parents relationship, in order to pursue the adolescent’s best inte-rest with relevant positive effects not only for their sexual and reproductive health.
Keywords: Adolescents; sexual and reproductive health services; respect for autonomy; bodily autonomy; informed consent